Sosialisasi Dagusibu (Dapatkan, Gunakan, Simpan, Buang) Obat Dengan Benar Di Kelurahan Bandengan, Kota Pekalongan - Khafid Mahbub; Mahfur Mahfur; Mochammad Ardy Wiyono; Noni Nur Ekayanti (Pusat Riset dan Inovasi Nasional, 2023)
Medicine are something that is very easy to get. However, the lack of knowledge about drug management from getting it to disposing of it can cause various problems. In an effort to improve health, it is necessary to provide optimal education to the public to increase the level of public awareness of health. The purpose of carrying out this service is to increase the awareness of the people of Bandengan village in DAGUSIBU medicine. The implementation method used is the lecture method or direct presentation and discussion to the public. The results show that the role of education can increase the knowledge of the community related to drug management, starting from how to get it to properly dispose of the drug. This is shown by the increase in pre-test and post-test scores with significant results.